2019
DOI: 10.1002/ijgo.12756
|View full text |Cite
|
Sign up to set email alerts
|

Using misoprostol to treat postpartum hemorrhage in home deliveries attended by traditional birth attendants

Abstract: Objective To explore the clinical and programmatic feasibility of using 800 μg of sublingual misoprostol to prevent and treat postpartum hemorrhage (PPH) during home delivery. Methods The present double‐blind randomized controlled trial included women who underwent home deliveries in Chitral district, Khyber Pakhtunkhwa province, Pakistan, after presenting at healthcare facilities during the third trimester of pregnancy between May 28, 2012, and November 27, 2014. Participants were randomized in a 1:1 ratio to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…Although the incidence of misoprostol‐induced high fever in Argentina is significantly lower than in Ecuador, both rates are still higher than high fever rates observed in other studies testing the same regimen conducted elsewhere [15‐18]. High fever rates from a multi‐country trial that systematically measured temperature at 60‐ and 90‐min post‐treatment with adjunct misoprostol (600 mcg sublingual) also warrant consideration [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the incidence of misoprostol‐induced high fever in Argentina is significantly lower than in Ecuador, both rates are still higher than high fever rates observed in other studies testing the same regimen conducted elsewhere [15‐18]. High fever rates from a multi‐country trial that systematically measured temperature at 60‐ and 90‐min post‐treatment with adjunct misoprostol (600 mcg sublingual) also warrant consideration [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, increased pyrexia associated with misoprostol, particularly the possibility for high fever (≥40.0°C /104°F), has evoked concerns among some providers [2,9‐12], prompting continued vigilance and investigation of misoprostol’s thermoregulatory effects [9]. A review of studies that report on high fever post‐treatment with sublingual misoprostol 800 mcg reveals that this effect is mostly negligible [13‐17], with the exception of a 36% high fever rate documented in Ecuador [18]. This rate is particularly striking when compared to rates ranging from 0 to 9% in the eight sites in four different countries that participated in two large multi‐country trials evaluating the safety and efficacy of 800 mcg sublingual misoprostol for PPH treatment [13‐14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Expansion of the National PPH Initiative to include health huts would equip lower-level and lay health workers who typically rely solely on referral to higher care with a means to prevent and treat PPH. Community-based studies have demonstrated that task-sharing PPH diagnosis and management with misoprostol to community health workers or birth attendants prior to referral is a safe and feasible model of care [5]. In Niger, stocking and training lay health providers to administer misoprostol for PPH management at the lowest levels of the health system could magnify the National PPH Initiative’s reach.…”
Section: Discussionmentioning
confidence: 99%
“…Misoprostol has been established as a viable alternative to oxytocin for both prevention and treatment of PPH and has been recommended for use in low-resource settings [3, 4]. Misoprostol can be self-administered by women after delivery to help prevent PPH, and is safe to use for treatment if excessive bleeding occurs [3–5]. In addition to uterotonics, other management options for addressing PPH in low resource settings have been identified, including the uterine balloon tamponade (UBT) and non-pneumatic anti-shock garment (NASG) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on misoprostol's known efficacy in treating hemorrhage from two large trials conducted in hospital settings (Blum et al 2010;Winikoff 2010), community-based studies have explored the potential of offering 800 mcg sublingual misoprostol for PPH treatment in home deliveries, administered by a community health worker or birth attendant prior to referral (Abbas et al 2019). These studies confirmed that lay workers can safely administer misoprostol therapeutically and also highlighted the need to make treatment available, particularly in light of the social and cultural challenges around referrals that were documented for women diagnosed with PPH in remote settings (Abbas et al 2019). Also, community-based research on use of misoprostol for prevention of PPH has documented rates of PPH from 6 to 16% despite receipt of prophylaxis (Abbas et al 2019;Mobeen et al 2011).…”
Section: Introductionmentioning
confidence: 99%